Pornography in print media: Legal review of pornographic content on Mantra Tabloid in Indonesia - Supadiyanto Supadiyanto (Journal of Social Studies (JSS), 2019)
Cases of pornography are rife in various media, including print media, into severe problems because pornographic content harms public behavior. Especially for teenagers and children. The main problem is: what is the legal review of pornographic content in the Mantra Tabloid? The research paradigm uses quantitative—data collection techniques by content analysis, documentation, and literature review. Two types of data are processed: primary data (document Mantra Tabloid of 170th Edition) and secondary data (literature study). The result, Tabloid Mantra legitimately contain pornographic content. The women exposed in the Mantra Tabloid became the object of sex as well as victims. The result of content analysis from Tabloid Mantra is corroborated by the Press Council's decision, which gives sanction (written warning). In the future, the research results should be followed up by a lawsuit against the managers of Tabloid Mantra through the court.